If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4(7 + 9) + 6m = 0 Combine like terms: 7 + 9 = 16 3 + -4(16) + 6m = 0 Multiply -4 * 16 3 + -64 + 6m = 0 Combine like terms: 3 + -64 = -61 -61 + 6m = 0 Solving -61 + 6m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '61' to each side of the equation. -61 + 61 + 6m = 0 + 61 Combine like terms: -61 + 61 = 0 0 + 6m = 0 + 61 6m = 0 + 61 Combine like terms: 0 + 61 = 61 6m = 61 Divide each side by '6'. m = 10.16666667 Simplifying m = 10.16666667
| 65+13t=-0 | | g/-7=-14 | | 2x-3=-x^2+4x+5 | | .6+.8x-4.8=19 | | -10+0.2500d=5 | | -2/5^3 | | -8p-6(6-3p)=5(p-4)-31 | | -10+0.2500d=-5 | | (a+8)(a-9)=0 | | y=-x^2+14x | | (X+2)(3x^2-6x+7)= | | 116+56+v=180 | | -10+0.2500d=0 | | 9x(x+1)=270 | | 2x^3+3x^2-7=0 | | -x+6=2x-9 | | 5/7x=32 | | -6x-16=20 | | 4x^2-4=-32 | | -=q/8-19 | | An=6n+1 | | 2x^2-14x=x+27 | | 4x/3=-3/4 | | 3/4=k(16) | | f(x)=e^3x-1 | | 84+48+2s=180 | | X+x+10+2x-20=180 | | -5+23=68 | | (m+2)=168 | | (5x+6)-(2x-7)= | | 91=7(X+7) | | 6x-7=3x+4+2x+1 |